Pre-spliceosome formation in S.pombe requires a stable complex of SF1–U2AF(59)–U2AF(23) - Huang, Tao (Oxford University Press, 2002)
We have initiated a biochemical analysis of splicing complexes in extracts from the fission yeast Schizosaccharomyces pombe. Extracts of S.pombe contain high levels of the spliceosome-like U2/5/6 tri-snRNP, which dissociates into mono-snRNPs in the presence of ATP, and supports binding of U2 snRNP to the 3′ end of introns, yielding a weak ATP-independent E complex and the stable ATP-dependent complex A. The requirements for S.pombe complex A formation (pre-mRNA sequence elements, protein splicing factors, SF1/BBP and both subunits of U2AF) are analogous to those of mammalian complex A. The S.pombe SF1/BBP, U2AF(59) and U2AF(23) are tightly associated in a novel complex that is required for complex A formation. This pre-formed SF1– U2AF(59)–U2AF(23) complex may represent a streamlined mechanism for recognition of the branch site, pyrimidine tract and 3′ splice site at the 3′ end of introns.